If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 2 = 2(3y + 1) Reorder the terms: 2 + 6y = 2(3y + 1) Reorder the terms: 2 + 6y = 2(1 + 3y) 2 + 6y = (1 * 2 + 3y * 2) 2 + 6y = (2 + 6y) Add '-2' to each side of the equation. 2 + -2 + 6y = 2 + -2 + 6y Combine like terms: 2 + -2 = 0 0 + 6y = 2 + -2 + 6y 6y = 2 + -2 + 6y Combine like terms: 2 + -2 = 0 6y = 0 + 6y 6y = 6y Add '-6y' to each side of the equation. 6y + -6y = 6y + -6y Combine like terms: 6y + -6y = 0 0 = 6y + -6y Combine like terms: 6y + -6y = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| d-9=-45 | | 25+x+5+34+x+-2=180 | | -8(s+1)=12 | | -10+x+70=180 | | yhi0jhttps://youtu.be/QT2l4Yw5TpUih8o9 | | 6y+2=2(3x+1) | | 68y-45=y-(-98) | | x+130+x+70=180 | | 20/5=7 | | .48/5.5 | | 5(2c+1)=10c | | -8+108+x=180 | | 3x^2+4=28 | | 3y=8x^2-6x | | 3/7x^2-3/14x-5/7 | | (-4a+3)+(-4a-6)= | | 108+x+x+88=180 | | 0.65x=x-1 | | 1m-1=9m+15 | | x-36+x-23+x=180 | | 93+-6+x=180 | | 1/2x-2=1/6x | | 12+x+1+13+x+-6=180 | | 0.65x=x-2 | | 15r^2+10rs+12rs+8s^2= | | 4(3s+3)=72 | | 66+x+57=180 | | 2.50XY+4XY=39 | | 3(a-1)=36 | | -15d-19d-5d-4d-6d=-18 | | 5x-(2+9x)=8-3x | | 2.50+X+4+X=39 |